Analisis Pembinaan di Yayasan Bina Muallaf Untuk Meningkatkan Nilai Keagamaan Para Muallaf di Kota Medan - Sumawan, Aldi Candra; Surya, Maulana Andi (UIR Press, 2023)
This research is the result of field research which aims to analyze the activities of Bina Muallaf in fostering converts and the effectiveness of Bina Muallaf in increasing the religion of converts. This research is a field research using descriptive qualitative method. Data collection techniques used in this study are observation, interviews, and documentation. Primary data sources in this study are administrators, supervisors, and converts. While the secondary data sources in this study were in the form of books by the Bina Muallaf Foundation at the Al-Muhajirin Bumi Asri Medan Mosque, as well as the results of documentation and results of books and journals that support this research. In a study there is data analysis, data analysis used in this study is data reduction (data reduction), data collection, and drawing conclusions (verification). This research resulted in a conclusion that the Effectiveness of the Muhajirin Bumi Asri Bina Muallaf Foundation has a program that really inspires many people so that each program implemented can increase the religious understanding of each convert, with each program Muallaf will receive coaching that can make each convert learn more about Islamic teachings long way to get ridho and be able to maintain consistency in carrying out the Islamic religion.